To Determine the Effect of An Oral Joint Supplement on Orthopaedic, Physiotherapy and Handler Evaluation Scores in Horses. (9th September 2013) - Murray, R.; Adams, V.; Walker, V.; Tranquille, C.; Copeman, S.; Spear, J.; Frost, R.; Marlin, D.
Abstract : Introduction: Despite the range of oral joint supplements available, there has been very limited research into their efficacy. Aims: To determine effect of an oral joint supplement on orthopaedic, physiotherapy and handler evaluation in horses. Methods: Twenty‐four mature horses were included in the study. Horses were excluded if they were in poor body condition, had health problems or greater than 2/5 lameness. Supplement Sa (containing chondroitin sulfate 1.62 g/100 kg bwt, glucosamine 1.9 g/100 kg bwt, vitamin C 0.8 g/100 kg bwt, methyl sulphonyl methane 2.56 g/100 kg bwt, DHA 0.66 g/100 kg bwt), EPA 0.34 g/100 kg bwt or placebo P (carrier/flavours only) were given to horses in their feed for 21 days each in a triple‐blind crossover design; all horses received supplement and placebo in random order. Horses were evaluated at Days 0 (baseline), 21 (after first treatment) and 42 (after second treatment). Assessments included: clinical orthopaedic evaluation for straight line and lungeing circle (walk and trot), and during ridden exercise (walk, trot and canter); handler field evaluation, during groundwork and while ridden, grading‐specific criteria; grading of range of motion (ROM) and muscle tone based on standardised physiotherapy criteria. All evaluators were blinded to treatment. Significance indicates P<0.05. Results: S was associated with significantly lower lameness grade in a straight line and circle than either P or baseline. Both S and P were associated with significantly improved ROM and muscle tone over baseline. Handler scores for ridden and groundwork were significantly higher with S compared with P or baseline. After S, horses were graded significantly higher for field 'ease‐of‐movement' compared with P or baseline. Conclusions and practical significance: Oral administration of this supplement was associated with less lameness, improved ridden/groundwork scores and improved 'ease‐of‐movement' in the field. Improvement in physiotherapy assessment with both treatments over time suggests effects of ongoing training on ROM and muscle tone. Ethical animal research: This study involved informed consent of the persons responsible for horses used in the study.Sources of funding: World Horse Welfare.Competing interests: David Marlin and Rebecca Frost are employed by Science Supplements. Vicki Adams and Rachel Murray are involved with Science Supplements on a consultancy basis.